Cutaneous human papillomavirus genotypes in different kinds of skin lesions in Argentina. Issue 2 (27th July 2016) - Correa, Rita Mariel; Vladimirsky, Sara; Heideman, Daniëlle A.M.; Coringrato, Mauro; Abeldaño, Alejandra; Olivares, Liliana; Del Aguila, Roxana; Alonio, Lidia Virginia; Snijders, Peter J.F.; Picconi, María Alejandra
Abstract : Cutaneous human papillomaviruses (HPVs) comprise a large and highly heterogeneous virus group. Some of the cutaneous HPVs of the genus Beta have been suggested as a co‐factor in the development of non‐melanoma skin cancer (NMSC). The aim of this study was to determine cutaneous HPV prevalence and type‐specific distribution in different kinds of skin lesions from Argentine patients visiting Dermatology Departments of three hospitals from Buenos Aires. A cross‐sectional analysis was performed. HPV DNA was analyzed in (i) 3 patients with Epidermodysplasia verruciformis (EV) harboring benign lesions (BL) (n = 1) and squamous cell carcinoma (SCC) (n = 4); (ii) 240 non‐EV patients harboring: (a) BL (n = 38), (b) Actinic Keratosis (AK) (n = 83), (c) SCC (n = 74), and (d) basal cell carcinoma (BCC) (n = 96). Detection and genotyping of 35 cutaneous HPV DNA was carried out by BGC‐PCR and GP5+/6 + PCR followed by reverse line blot assay. In EV patients, Beta types were found in all lesions (5/5), including the potentially high‐risk HPV types 5 and 8, mostly in multiple infections. In non‐EV patients, cutaneous types were found in 50.0% of BL, 43.4% of AK, 31.1% of SCC, and 16.7% of BCC. Beta HPVs were the most frequently found in all lesions, being present in all AK and SCC cases that were positive for HPV. No type‐specific correlation with lesion severity was found. In our series, a wide spectrum of cutaneous HPV types was detected in different skin lesions. A possible role for these HPVs in skin carcinogenesis deserves further study. J. Med. Virol. 89:352–357, 2017 . © 2016 Wiley Periodicals, Inc.